Unpacking the political economy of fertilizer subsidy reforms - Chugh, Aditi; Resnick, Danielle (International Food Policy Research Institute, 2025)
Global calls to repurpose agricultural support toward more sustainable and equitable food systems have intensified scrutiny of fertilizer subsidies. While political economy constraints often hinder reform, the exact manifestation of these constraints is rarely examined. To clarify the specific mechanisms at play, this paper systematically reviews peer-reviewed studies from 2000 to 2025 and identifies 38 fertilizer subsidy reform cases across 15 countries. We code political economy factors influencing outcomes at different stages of subsidy adoption and redesign. The analysis shows that ideational factors around self-sufficiency, the private sector, and the social contract, as well as the institutional structures impacting policymaking, are central to successful subsidy introduction. Electoral incentives play a role at both the policy introduction and redesign phases. Yet, political economy factors are not the only prominent drivers. In fact, technocratic considerations about underperformance or corruption became more prominent during redesign efforts but were also present in more than 80 percent of failed cases. This reaffirms that while technocratic factors, including the availability of research and evidence are necessary for subsidy design improvements, they are not sufficient on their own. By distinguishing which political economy factors matter and how they interact with broader policy process dynamics, this study provides a more actionable foundation for anticipating and managing challenges to fertilizer subsidy reforms and repurposing more broadly.